A Study on Consumer Behavior and Effect of Usage of Smartphone Amongst Undergraduate University Students - Varsha Ganatra; Dwi Nita Aryani; Shiang Lan Low; Daisy Mui Hung Kee; Mahotari Madhusmithii; Maisarah Said; Mohamad Ali Imran; Manvi Poojary (Advances in Global Economics and Business Journal, 2021)
This study aims to analyze the consumer (students) behavior towards smartphones and the positive or negative effect of smartphone usage by concentrating on academic performance. This study was conducted by distributing the questionnaire among undergraduate university students in India and Malaysia, consisting of 100 students (50 Indian and 50 Malaysian students). Based on the findings, time spent on smartphones and the motive for using smartphones are largely attributable to the daily productivity of students.